The Role of KLF4 in Alzheimer’s Disease - Cheng, Ziqian; Zou, Xiaohan; Jin, Yang; Gao, Shuohui; Lv, Jiayin; Li, Bingjin; Cui, Ranji (Frontiers in Cellular Neuroscience, 2018)
Krüppel-like factor 4 (KLF4), a member of the family of zinc-finger transcription factors, is widely expressed in range of tissues that play multiple functions. Emerging evidence suggest KLF4’s critical regulatory effect on the neurophysiological and neuropathological processes of Alzheimer's disease (AD), indicating that KLF4 might be a potential therapeutic target of neurodegenerative diseases. In this review, we will summarize relevant studies and illuminate the regulatory role of KLF4 in the neuroinflammation, neuronal apoptosis, axon regeneration and iron accumulation to clarify KLF4’s status in the pathogenesis of AD.